The Urgency of Islamic Investment Literacy in Managing Muslim Personal Finance - Zamroni Alpian Muhtarom; Adrianda Anwar; Abdurrahman Abdurahman; Mohammad Najib Roodhi (CV. Abhinaya Indo Group, 2025)
The Islamic finance industry has demonstrated positive growth trends in Indonesia. However, the level of literacy regarding Islamic investment remains relatively low, especially among Muslim individuals. A limited understanding of Sharia-compliant investment principles and instruments has led to suboptimal financial decisions that may conflict with Islamic values. This study aims to explore the urgency of Islamic investment literacy within the context of personal financial management for Muslims and to identify key challenges and strategies for improvement. Employing a qualitative approach through literature analysis, this article examines the concepts of financial literacy in Islamic perspective, types of Sharia-compliant investment instruments, and factors influencing individuals’ understanding of Islamic investment products. The findings reveal that Islamic investment literacy is not only an economic necessity but also a spiritual obligation grounded in the Maqāṣid al-Sharīʿah, especially the principle of safeguarding wealth (ḥifẓ al-māl). The study recommends that stakeholders—governments, financial institutions, and educational bodies—collaborate to develop structured and sustainable strategies for enhancing Islamic financial literacy